Long Term Effects of COVID-19 among RT-PCR Positive Bangladeshi Patients - Islam, Neena; Rahim, Mohammed Abdur; Das, Prabir Kumar; Mostafa, Golam; Alam, A K M Manzurul (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: COVID-19 was an unknown disease previously. This pandemic has affected almost all countries of the world and creating a deadly experience to all. It leads to long term squeals among many affected people with consequent loss of productivity and quality of life. This entity is called long COVID syndrome. The objectives of the present study is to find out the long term sequels of COVID-19 patients. Materials and methods: This was an observational study where a total of 56 patients of COVID-19 were recruited. Demographic data and long term sequelae were recorded from these patients. All the patients were confirmed cases of COVID-19 by RT-PCR. Prior consent from the patients and ethical clearance was taken. Data were analyzed by SPSS-20. Results: Among 56 cases male was 31(55.4%) and female was 25(44.6%). Male to female ratio was 1.24:1. Age group distribution showed <20 years was 4(7.1%), 21-30 years was 10(17.9%) 31-40 years was 12(21.4%) 41-50 years was 14(25.0%) and 51-60 years was 16(28.6%) Regarding occupation majority were service holder 34(60.7%).Fifty two(92.9%) were from urban areas Among 56 cases 48(85.7%) took treatment at home for COVID-19. Regarding vaccination history 4(7.1%) got no vaccination 18(32.1%) took Astra-Zenaca, 12(21.4%) took Moderna Biotech and 22(39.3%) took Sinovac vaccine. Regarding analysis of postcovid sequelae among 56 cases 25(44.6%) had fatigue, 7(12.5%) had cough, 4(7.1%) had shortness of breath, 12(21.4%) had chest pain or tightness, 22(39.3%) had memory impairment, 8(14.3%) had insomnia, 22(39.6%) had joint pain, 8(14.3%) had muscle pain or headache, 8(14.3%) had palpitation and 16(28.6%) had minor psychiatric illness like,depression or anxiety. Conclusion: Present study showed post COVID complications among significant number of COVID-19 patients.Thus COVID-19 is not only associated with loss of life but also with long term complications and loss of productivity that needs proper attention. JCMCTA 2021 ; 32 (2) : 30-33